Moral intelligence and its self-esteem among a sample of Colleges of Education and Engineering Informatics at the University of Damascus students (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to reveal the relationship between moral intelligence and self-esteem among a sample of third-year students in the College of Education and Engineering Informatics at the University of Damascus, also it aims to find out the differences between third-year students in the College of Education and Engineering Informatics at the University of Damascus in moral intelligence and self-esteem depending on the variable Specialization (psychological counseling, Informatics Engineering), and variable sex (male and female), has formed research sample of 310 students from the third year students in the College of Education and Engineering Informatics at the University of Damascus, distributors to (72) to guide myself and (238) Engineering Informatics, randomly selected class of the College of Education and Informatics Engineering at Damascus University. The measure applied to them moral intelligence and a measure of self-esteem of the researcher after the Pttbaiqama the exploratory sample confirmed Sedkhma and Thbathma. Search results indicated: - The presence of D. statistically link between moral intelligence and self-esteem among a sample search and individuals amounted to link value (0.76(. - There were no statistically significant differences between the academic specialization psychological counseling and Engineering Informatics in moral intelligence. - There were no statistically significant differences between the academic specialization psychological counseling and Engineering Informatics in self-esteem. - The presence of a statistically significant gender differences in male and female moral intelligence in favor of females. - The presence of a statistically significant gender differences in male and female self-esteem in favor of females.